TENSES ANALYSIS OF Q.S. AL-IKHLAS AL-FALAQ AND AN-NAS - zainudin saragi M.HUM (JURNAL LINER (Language Intelligence and Educational Research), 2021)
The research analyzes Tenses of Q.S. Al-Ikhlas, Al-falaq and An-nas in their English translations. There the objective study of this research like: 1) To know what are tenses in Q.S.Al-Ikhlas, Al-falaq and An-nas in their English translations. 2) To know kinds of tenses in Q.S. Al-Ikhlas, Al-falaq and An-nasin their English translation. Thus, it is library research based content analysis which is describing Tenses of Q.S. Al-Ikhlas, Al-Falaq, and An-Nas in their English translation. Moreover, the researcher uses documentation technique to collect the data and content analysis technique to analyze the data. In conclusion, the researcher finds 3 tenses used in Qs. Al-Ikhlas, Al-falaq and An-nas there are: simple present tense, simple past, and present perfect tense. The research results are: There are 3 Simple presents for Q.S Al-Ikhlas, 1 Simple present and 3 Simple past for Q.S. Al-Falaq, and 2 Simple presents for Q.S. An-Nas. Keyword: Analysis, tenses, AL Qur’an